The 11-Year Prognostic Impact of Chronic Total Occlusion in the Noninfarct-Related Coronary Artery on Patients with Acute Myocardial Infarction - Xuanqi An; Jingang Yang; Kefei Dou; Yuejin Yang (Journal of Interventional Cardiology)
Background. The prognostic significance of CTO in the non-IRA in patients with AMI has been under dispute. Relevant long-term follow-up studies are lacking. Hypothesis. CTO in the non-IRA is an independent predictor of poor long-term prognosis in patients with AMI. Methods. We prospectively enrolled 2336 patients with AMI who received emergent percutaneous coronary intervention successfully from January 2006 to May 2011. Our primary endpoints included death from cardiovascular causes, recurrent myocardial infarction, stroke, and target-vessel revascularization. We adopted Cox regression analysis adjusted for confounders to analyze the impact of CTO in the non-IRA on long-term mortalities. Results. We identified 628 (27.6%) subjects with CTO in the non-IRA among 2282 AMI patients. After a mean follow-up duration of 134.3 months, we found the CTO group had significantly higher MACCE rate than the group without CTO (30.4% versus 24.3%, P=0.004). CTO in the non-IRA independently predicted 11-year MACCE in the male AMI subgroup (hazard ratio 1.28, 95% confidence interval 1.06 to 1.54, P=0.01) and in the male NSTEMI subgroup (hazard ratio 1.53, 95% confidence interval 1.09 to 2.15, P=0.02). In the CTO group, three-vessel disease independently predicted 11 year MACCE (hazard ratio 2.05, 95% confidence interval 1.29 to 3.28, P=0.002). Conclusions. Our long-term observational study supported the association between CTO in the non-IRA and poorer prognosis in AMI patients undergoing primary PCI. We identified the group with the three-vessel disease as a high-risk subgroup in patients with CTO in the non-IRA.